THE EFFECT OF 5E LEARNING CYCLE MODEL TO STUDENTS’ CONCEPT CONSTRUCTION ON ENVIRONMENTAL POLLUTION MATERIAL - Dini Afriansyah; Kartadikarya .; Indah Wigati (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
This study aims to determine the effect of Learning Cycle 5E learning model on the mastery of students' concepts on VII class in environmental contents. Variable in this research is Learning Cycle 5E learning model as independent variable and mastery of concept as dependent variable. The sample of this research is VII class 3 as experiment class and VII.4 class as control class. This study is a quasi experiment with Non-equivalent Control Group Design research design, while data collection techniques used are interview, written test (pretest-postest) and documentation. The written test (pretest-postest) is used to see students' mastery skills after applied Learning Cycle 5E learning model. Analysis of test data using t-test with a significant level of 5%. Based on hypothesis test of control class data and experimental class hence obtained sig value 0,000<0,05, significantly different. The overall experimental class posttest score can be said to be excellent, with an average gain of 84.00, while the mean value of the control class is 73.33. Based on this it can be concluded that there is a significant effect of the implementation of Learning Cycle 5E learning model on the mastery of students' concepts on environmental VII class. Keywords: learning model, learning cycle, 5E, concept mastery